Â¬PENINGKATAN KETERAMPILAN MENYIMAK SYAIR MENGGUNAKAN METODE DISCOVERY LEARNING DENGAN MEDIA AUDIO VISUAL - Jaya, Hilarius Frendi; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the low acquisition of student scores on listening to poetry. The author takes an action through the discovery learning method with audio visual media to improve poetry listening skills. The purpose of this study is to describe the planning, implementation and results of listening to poetry using the discovery learning method with audio visual media. The method used in this research is descriptive form of classroom action research. This study was conducted in 2 cycles, the procedure for conducting research in each cycle consists of planning, implementing, observing and reflecting learning. The results obtained from this study include: in the first cycle of planning that is equal to 68 (good enough) in the second cycle to 96 (very good). The results of the implementation in the first cycle were 77 (good enough) in the second cycle to 93 (very good). The average results of listening to poetry in the first cycle were 70,96 (good enough) in the second cycle to 80.82 (good). The results of student attitudes assessment include: honest, discipline, responsibility, tolerance in the first cycle of 67.45 (good enough) and in the second cycle to 79.16 (good enough).Â Key words: Poetry Listening Skills, Discovery Learning Method, Audio Visual